2017
DOI: 10.1177/0738894216688894
|View full text |Cite
|
Sign up to set email alerts
|

Democratic values and the microfoundations of Arab support for peace with Israel

Abstract: Israel. These findings demonstrate that contrary to the claims of skeptics, democratization and peace can reinforce each other in the Arab world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…An impressive earlier body of research, which focused on Western public opinion on international intervention (Clements, 2012(Clements, , 2014Davies and Johns, 2016;Falomir-Pichastor et al, 2012;Reifler et al, 2014), has already shown how attitudinal profiles can explain support for various types of foreign interventions. In the context of the burgeoning research on pro-democracy attitudes among Arab publics (Berger, 2019a;Tessler et al, 2012), there are only few examinations of how and whether this might correlate with views on international politics (Berger, 2019b;Ciftci and Tezcür, 2016;Spierings, 2014;Tessler and Nachtwey, 1998). We are thus left with looking at published opinion and (social) media discourses as a first gauge of how views of democracy might affect support for different forms of intervention in Syria.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…An impressive earlier body of research, which focused on Western public opinion on international intervention (Clements, 2012(Clements, , 2014Davies and Johns, 2016;Falomir-Pichastor et al, 2012;Reifler et al, 2014), has already shown how attitudinal profiles can explain support for various types of foreign interventions. In the context of the burgeoning research on pro-democracy attitudes among Arab publics (Berger, 2019a;Tessler et al, 2012), there are only few examinations of how and whether this might correlate with views on international politics (Berger, 2019b;Ciftci and Tezcür, 2016;Spierings, 2014;Tessler and Nachtwey, 1998). We are thus left with looking at published opinion and (social) media discourses as a first gauge of how views of democracy might affect support for different forms of intervention in Syria.…”
Section: Hypothesesmentioning
confidence: 99%
“…In order to test hypothesis 1, we use a question that explicitly asks about the preference for democracy over authoritarian rule (Table 3). Such comparison between democracy and authoritarian alternatives has increasingly been employed in research seeking to examine the link between pro-democracy attitudes and foreign policy attitudes in the Middle East (Berger, 2019b; Ciftci and Tezcür, 2016; Köse et al, 2016). We thus compare respondents who preferred a ‘strong leader’ (‘1’) with those who thought that democracy was the best way to solve their country’s problems (‘0’).…”
Section: Independent Variablesmentioning
confidence: 99%